SMPS loop stability design - Norfariha Farwani Sulaiman
The Mathcad is being used very widely in both electronic industries and educational institutions as an essential computer-aided-design (CAD) tool for mathematical application. Engineers using Mathcad will easily simulate mathematical application into graph or other application. Instead of using various computer-aided designs (CAD) to make the calculation and plot graph, this software amazingly can do both applications simultaneously.